2014
DOI: 10.1016/j.scitotenv.2014.04.042
|View full text |Cite
|
Sign up to set email alerts
|

Predicting PCB concentrations in cow milk: validation of a fugacity model in high-mountain pasture conditions

Abstract: A fugacity model reported in the literature was applied to a high-altitude pasture in the Italian Alps. The model takes into account three compartments (digestive tract, blood and fat tissues) in unsteady-state conditions using food as the contamination source. Disregarding biotransformation inside cow tissues, the predicted concentrations of 14 polychlorinated biphenyls (PCBs) in milk were in good agreement with the observed data, especially for congeners known for their resistance to biotransformation (e.g.,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 43 publications
(103 reference statements)
0
20
0
Order By: Relevance
“…However, a variety of adverse effects of the so called "dioxin-like" PCBs have been observed. They cause the reproductive disorders in men and women (Toft, 2014;Sumner et al, 2019), liver dysfunctions (Boucher et al, 2015;Deng et al, 2019), immunosuppression (Leijs et al, 2009), neurological effects (Giuda et al, 2017;Berghuis and Rose, 2019) and thyroid disorders (Hagmar et al, 2001;Gaum et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a variety of adverse effects of the so called "dioxin-like" PCBs have been observed. They cause the reproductive disorders in men and women (Toft, 2014;Sumner et al, 2019), liver dysfunctions (Boucher et al, 2015;Deng et al, 2019), immunosuppression (Leijs et al, 2009), neurological effects (Giuda et al, 2017;Berghuis and Rose, 2019) and thyroid disorders (Hagmar et al, 2001;Gaum et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Seven PCB congeners (PCB 28,52,101,118,138,153,180) are often found in the environment and human food in Europe and all around the world. Tremolada et al (2014) reported that PCB absorption differs depending on the breeding conditions. If the cows are bred in the cowshed, the PCB absorption rate is higher than in the alpine conditions.…”
Section: Introductionmentioning
confidence: 99%
“…1). In addition, CB-209 was found only in soil, not in the air, vegetation or cow's milk from the same area (Tremolada et al 2014). The origin of this congener in this mountain environment is difficult to explain.…”
Section: Pcb Levels In Soilmentioning
confidence: 87%
“…Soil, silage, hay and pasture can become polluted by PCB and PBDE contaminated sewage sludge run off from waste water treatment plants, older coatings of silos and air-soil deposition from industrial emissions [3537]. Fugacity models depicting vegetation-to-milk, air-to-grass, and grass silage-to-lactating dairy cow transfer rates have shown that contaminated feed represents the greatest source for PCBs and PBDEs in lactating cows, while transfer via air and water is almost negligible [38]. Once absorbed, PCBs and PBDEs are rapidly distributed to tissues and milk.…”
Section: Introductionmentioning
confidence: 99%